Fun at Work, Less Job Stress by using Humour - Dayang Kartini, Abang Ibrahim; Sheilla Lim, Omar Lim (2011)
A fun place at work is more productive than a normal workplace; little empirical research has effectively addressed the impact of fun at work on job stress, particularly in Malaysia context. This study explored the employees’ perception regarding the effect of using humour in workplace to reduce job stress. This study also identified the causes of job stress and most type of humour used by employees if they feel stress at work. This sample included 6 staffs, male and female from private company ranging from 31 to 40 years of age. The researchers used the interview technique for collecting the data. An interview inventory was prepared before hand and its validity was checked in consultation with other researcher and experts in the university. The findings showed that all participants feel stress with their job and the use of humour is able to reduce their stress at workplace. All participants preferred to use verbal humour when they feel stress at workplace because it increases individual’s self esteem, work quality and work spirit. Apart from that, benefit of humour is also to build rapport and initiate friendship.